Chebyshev Polynomial-Based Authentication Scheme in Multiserver Environment. (25th August 2020) - Truong, Toan-Thinh; Tran, Minh-Triet; Duong, Anh-Duc
Abstract : Nowadays, communication technologies are more and more strongly advanced, such as 4G or 5G. There are many useful online applications, and one of them is the telecare medical information system (TMIS). If the TMIS is widely deployed, patients and doctors will have more frequently connection. Clearly, this enhances our quality of life. One of the most important modules securely constructing this convenient TMIS is the user-authentication scheme. We should prevent user identity and related information from the adversary's eavesdropping. Therefore, the authentication scheme could provide user anonymity and concern some kinds of attacks, such as impersonation or password-guessing attacks. Common solutions are a combination of hash function and public-key cryptosystem (RSA or elliptic curve cryptosystem, ECC), but current schemes do not consider identity protection as one main task necessary for medical information environment. In this paper, our results consist of some important analyses of previous works and a multiserver user-authentication scheme suitable for TMIS using Chebyshev polynomial with two models: random oracle and BAN-logic.